How the IMF By Induces a Local By Component During Northward IMF Bz and Characteristic Timescales. Issue 5 (2nd May 2018) - Tenfjord, P.; Østgaard, N.; Haaland, S.; Snekvik, K.; Laundal, K. M.; Reistad, J. P.; Strangeway, R.; Milan, S. E.; Hesse, M.; Ohma, A.
Abstract: We use the Lyon‐Fedder‐Mobarry global magnetohydrodynamics model to study the effects of the interplanetary magnetic field (IMF) B y component on the coupling between the solar wind and magnetosphere‐ionosphere system when IMF B z >0. We describe the evolution of how a magnetospheric B y component is induced on closed field lines during these conditions. Starting from dayside lobe reconnection, the magnetic tension on newly reconnected field lines redistribute the open flux asymmetrically between the two hemispheres. This results in asymmetric magnetic energy density in the lobes. Shear flows are induced to restore equilibrium, and these flows are what effectively induces a local B y component. We show the radial dependence of the induced B y and compare the results to the induced B y during southward IMF conditions. We also show the response and reconfiguration time of the inner magnetosphere to IMF B y reversals during northward IMF B z . A superposed epoch analysis of magnetic field measurements from seven Geostationary Operational Environmental Satellite spacecraft at different local times both for negative‐to‐positive and positive‐to‐negative IMF B y reversals is presented. We find that the induced B y responds within 16 min of the arrival of IMF B y at the bow shock, and it completely reconfigures within 47 min. Key Points: We present a dynamic description of how B y is induced during northward directed IMF Asymmetries in magnetic energy density drives shear flows The magnetosphere response and reconfiguration time are comparable to southward IMF